2002
DOI: 10.1074/jbc.m206951200
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Arrestin into the Active Receptor-binding State Requires an Extended Interdomain Hinge

Abstract: Arrestins selectively bind to the phosphorylated activated form of G protein-coupled receptors, thereby blocking further G protein activation. Structurally, arrestins consist of two domains topologically connected by a 12-residue long loop, which we term the "hinge" region. Both domains contain receptor-binding elements. The relative size and shape of arrestin and rhodopsin suggest that dramatic changes in arrestin conformation are required to bring all of its receptorbinding elements in contact with the cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 30 publications
7
112
0
1
Order By: Relevance
“…In view of strong experimental support for one-to-one arrestin-receptor interaction, bindinginduced conformational changes in arrestin were expected to make the receptor-binding surface more compact, largely by the proposed movement of the two arrestin domains (47). This model was supported by the findings that progressive deletions in the interdomain hinge reduced the ability of all arrestins to bind receptors (32,48). However, the data presented here reveal only subtle changes in the interdomain distances, ruling out a large clam shell-like relative motion of the N and C domains (16), but a small rotation of one domain relative to the other about the long axis could occur.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In view of strong experimental support for one-to-one arrestin-receptor interaction, bindinginduced conformational changes in arrestin were expected to make the receptor-binding surface more compact, largely by the proposed movement of the two arrestin domains (47). This model was supported by the findings that progressive deletions in the interdomain hinge reduced the ability of all arrestins to bind receptors (32,48). However, the data presented here reveal only subtle changes in the interdomain distances, ruling out a large clam shell-like relative motion of the N and C domains (16), but a small rotation of one domain relative to the other about the long axis could occur.…”
supporting
confidence: 74%
“…1). The addition of extra residues to the hinge does not affect P-Rh* binding, whereas increasing deletions progressively reduces the ability of arrestin-1 to bind P-Rh* (32). This suggested that the transition of arrestin-1 to the active receptor-bound state requires an extended hinge, which led to the idea that the domains move relative to each other, closing in on the receptor (the "clam-shell" model) (16).…”
mentioning
confidence: 99%
“…Release of the C tail is one of the major conformational changes occurring during arrestin activation as suggested by the sequential multisite binding model (17) and confirmed by EPR (24) and NMR (20) spectroscopic studies. The recent crystal structure of p44 arrestin-1, lacking the arrestin C tail, revealed marked conformational changes compared with a previous structure of p44 arrestin-1 (25), including a 20°rotation between the C and N domains (9) as had previously been suggested based on arrestin truncations (26) and molecular modeling (27). It is yet unclear to what extent this structure represents arrestin in the receptorbound conformation.…”
Section: Resultsmentioning
confidence: 75%
“…The first report suggested that in response to GPCR activation arrestin-3 binds JNK3␣2 and ASK1, whereas the recruitment of MKK4, which is necessary to make a complete signaling module, was believed to be indirect (6). Subsequent work showed that arrestin-3 promotes JNK3␣2 phosphorylation independently of GPCRs (7)(8)(9)11), in agreement with the finding that conformationally biased arrestin mutants, both the pre-activated 3A form with enhanced propensity to bind GPCRs (43-47) and the one "frozen" in basal-like conformation with impaired ability to bind receptors (11,48,49), interact with JNK3␣2 similarly to WT arrestin-3 (26,49). Arrestin-3 was also shown to co-immunoprecipitate with MKK4 essentially as efficiently as with ASK1 and JNK3␣2 (8,9,11).…”
Section: Arrestin-3 Promotes Activation Of Jnk1 and Jnk2mentioning
confidence: 65%